Answers

2015-09-16T13:37:39+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Ill just demonstrate the solution for you,
m^2 +12m = 3
m^2 + 12m + 36 = 3 + 36
(m + 6)^2 = 39
get the square root of both sides, then it will become
m +6 = square root of 39
m = -6 square root of 39
0
  • Brainly User
2015-09-16T16:08:02+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
M² + 12m + (12/2)² = 3 + (12/2)²
m² + 12 m + (6)² = 3 + (6)²
m² + 12m + 36 = 3 + 36
(m + 6)² = 39
 \sqrt{(m+6) ^{2} } = \sqrt{39}
m+6 =  + or - \sqrt{39}

m = -6- \sqrt{39}   or
m = -6 + \sqrt{39}
0